Does China’s emission trading scheme promote industry-level green innovation: evidence from Guangdong pilot market - Zhou, Kaiguo; Guan, Zihuan; Lu, Yunzhi (Frontiers in Environmental Science, 2023)
Green innovation has been the crucial and fundamental channel for efficient emission reduction and high-quality realization of the "Dual Carbon" goals. This paper provides novel evidence for the industry-level effect of Emission Trading Scheme (ETS) on green innovation. Specifically, we demonstrate both theoretically and empirically that the ETS has an overall significant promotion effect on green innovation both in compliance and non-compliance industries. Surprisingly, the promotion effect in non-compliance industries will be stronger, forced by the costs pass-through from up-stream compliance industries. Furthermore, we also find that the carbon price level can amplify the positive effect of the ETS on industry green innovation in the short run, while the price volatility weakens the effect of the ETS in the long run. Our findings shed light on the inherent effects of ETS on green innovation and suggest that policy-makers should stabilize the carbon prices so as to encourage green innovation.